1986
DOI: 10.2307/1590636
|View full text |Cite
|
Sign up to set email alerts
|

Triton X-100-Solubilized Mycoplasma gallisepticum and M. synoviae ELISA Antigens

Abstract: Triton X-100-solubilized Mycoplasma gallisepticum and M. synoviae ELISA antigens were found to be more specific and sensitive than six other antigens at a concentration of 250 ng protein/0.1 ml per microtiter plate well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The obtained results of both whole antigen or sonicated antigen gave similar results and good binding affinity for the surface of the microtiter plates polystyrene wells, which go parallel to Optiz and Cyr 12 results that recorded strong adsorbing affinity to the surface of the microtiter plates polystyrene wells at prepared the myco-ELISA antigen from disrupted M.gallisepticum or whole bacterial cell.…”
Section: Discussionsupporting
confidence: 77%
“…The obtained results of both whole antigen or sonicated antigen gave similar results and good binding affinity for the surface of the microtiter plates polystyrene wells, which go parallel to Optiz and Cyr 12 results that recorded strong adsorbing affinity to the surface of the microtiter plates polystyrene wells at prepared the myco-ELISA antigen from disrupted M.gallisepticum or whole bacterial cell.…”
Section: Discussionsupporting
confidence: 77%
“…However cross reactions were demonstrated by others (Opitz & Cyr, 1986;Higgins & Whithear, 1986;Bradley et al, 1988).…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have reported increased sensitivity of M. synoviae ELISAs using different antigen preparations (Opitz et al, 1983;Patten et al, 1984;Higgins & Whithear, 1986;Opitz & Cyr, 1986;Avakian & Kleven, 1990;Gurevich et al, 1995) ; however, specificity continues to be a problem associated with M. synoviae ELIS As.…”
Section: Discussionmentioning
confidence: 99%
“…A number of earlier studies of M . synouiae ELISAs used crude membrane preparations (Opitz et al, 1983;Patten et al, 1984;Higgins & Whithear, 1986), produced by either osmotic lysis or sonication of whole cells, or Triton X-100-solubilized membrane proteins (Opitz & Cyr, 1986) of M . synouiae, as antigens.…”
Section: Introductionmentioning
confidence: 99%